Efeito de Bifidobacterium longum 51A e Weissella paramesenteroides WpK4 em giardíase experimental - Joice de Freitas Fonseca (2015)
Giardiasis is a disease caused by the protozoan Giardia lamblia, non-invasive pathogenic parasite that infects 280 million people annually worldwide. The introduction of probiotics in the treatment of various diseases have increased in recent decades due to the benefits generated in the health of the host. Much of the probiotic strains with antimicrobial properties and immunomodulatory proven, are lactic acid bacteria that in microaerophilic. Given the above, we decided to evaluate the effect of probiotics on Giardia lamblia in experimental infections. Probiotics Bifidobacterium longum 51A were studied and Weissella paramesenteroides WpK4, this very last newly isolated and still in evidence phase of its probiotic function. We used 60 gerbils, males and females, divided into 6 groups: B. longum 51A with Giardia (BLi); group B. longum 51A without Giardia (BLC); W. paramesenteroides group with Giardia (WPi); W. paramesenteroides group without Giardia (WPC); infection control group (C); control group (CC). Animals received probiotic (B. longum 51A or W. paramesenteroides WpK4), 0.9% saline in the amount of 0.1 mL daily, and Giardia lamblia suspension by gavage. After 10 days of daily treatment with probiotics groups of animals BLi, WPi and Ci were infected with G. lamblia were euthanized on the seventeenth day after initiation of the experiment. For histological analysis, the duodenum of the small intestine was collected, fixed and designed to obtain sections stained with H & E and PAS. The villus height, crypt, the relationship crypt / villus, mucus area and area of immunostained trophozoites were calculated using the software installed in KS300 by Carl Zeiss image analyzer. The results were generated with GraphPad PRISM ® 4 software (GraphPad Software Inc.). In all tests were considered statistical difference values with significance level of 5% (p <0.05). The height of the intestinal crypts increased significantly in infected groups (Ci), (BLi) and (WPi) compared to the other experimental groups. We observed that the relationship crypt / villus was significantly higher in the infected group (Ci), (BLi) and (WPi) when compared to the others. The analysis of trophozoites immunomarked area showed a significant reduction in the number of trophozoites BLi and WPi groups in relation to Ci group. As for PAS positive area observed that in the group BLi the positive PAS regions in the crypts and villi was significantly higher compared to BLC groups, WPC, WPi. This study demonstrated that administration of probiotic bacteria (B. longum 51A and W. paramesenteroides) reduced the animal load infected with G. lamblia.